Combined kinesiotherapy in the rehabilitation of osteoarthritis patients after COVID-19 - Olena Voloshyna; Iryna Balashova; Ihor Lysyi; Olga Dykova; Larysa Kovalchuk (Physical Rehabilitation and Recreational Health Technologies, 2026)
Purpose. Osteoarthritis (OA) remains the most prevalent musculoskeletal disorder globally. Patients with OA and concomitant post-COVID syndrome may exhibit a more severe disease course, characterized by frequent exacerbations and enhanced joint inflammation. This study aimed to improve the effectiveness of rehabilitation in patients with osteoarthritis of large joints who had previously experienced COVID-19 by developing and implementing differentiated methods of combined kinesiotherapy. Materials & Methods. The study cohort included 72 patients (aged 36–62 years) with knee and hip osteoarthritis who had a history of COVID-19 and presented with post-COVID syndrome. Patients were randomly assigned to two groups: the control group (Group I, n=36) received basic therapy combined with standard therapeutic physical activity, while the intervention group (Group II, n=36) underwent a specialized, differentiated combined kinesiotherapy program alongside basic therapy. The comprehensive examination algorithm included clinical assessment, the Lequesne algofunctional index, the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), the EuroQol-5D-5L (EQ-5D-5L) questionnaire, and the Post-COVID-19 Functional Status (PCFS) scale. Results. Evaluation of the personalized combined kinesiotherapy course revealed functional capacity, quality of life, and post-COVID status improvements in both groups. However, the intervention group demonstrated a highly significant therapeutic advantage across all evaluated parameters (p